Anxiety and depression in patients with endometriosis: impact and management challenges - Laganà AS; La Rosa VL; Rapisarda AMC; Valenti G; Sapia F; Chiofalo B; Rossetti D; Ban Frangež H; Vrtačnik Bokal E; Vitale SG (Dove Medical Press, 2017)
Antonio Simone Laganà,1 Valentina Lucia La Rosa,2 Agnese Maria Chiara Rapisarda,3 Gaetano Valenti,3 Fabrizio Sapia,3 Benito Chiofalo,1 Diego Rossetti,4 Helena Ban Frangež,5 Eda Vrtačnik Bokal,5 Salvatore Giovanni Vitale1 1Unit of Gynecology and Obstetrics, Department of Human Pathology in Adulthood and Childhood “G Barresi”, University of Messina, Messina, 2Unit of Psychodiagnostics and Clinical Psychology, 3Department of General Surgery and Medical Surgical Specialties, University of Catania, Catania, 4Department of Maternal and Child Health, Gavardo Hospital, Brescia, Italy; 5Department of Reproduction, University Medical Center Ljubljana, Ljubljana, Slovenia Abstract: Endometriosis is one of the most common gynecological diseases and affects ~10% of women in reproductive age. The most common clinical signs of endometriosis are menstrual irregularities, chronic pelvic pain (CPP), dysmenorrhea, dyspareunia and infertility. Symptoms of endometriosis often affect psychological and social functioning of patients. For this reason, endometriosis is considered as a disabling condition that may significantly compromise social relationships, sexuality and mental health. Considering this point, the aim of this narrative review is to elucidate the impact of anxiety and depression in the management of women with endometriosis. Psychological factors have an important role in determining the severity of symptoms, and women who suffer from endometriosis report high levels of anxiety, depression and other psychiatric disorders. In addition, endometriosis is one of the most important causes of CPP; women with endometriosis suffer from a wide range of pelvic pain such as dysmenorrhea, dyspareunia, nonmenstrual (chronic) pelvic pain, pain at ovulation, dyschezia and dysuria. Several studies have underlined the influence of CPP on quality of life and psychological well-being of women with endometriosis. Data suggest that the experience of pelvic pain is an important component of endometriosis and may significantly affect emotive functioning of affected women. It has been demonstrated that high levels of anxiety and depression can amplify the severity of pain. Further studies are needed to better understand the relationship between psychological factors and perception of pain. Treatment of endometriosis may be hormonal or surgical. Surgery is the primary treatment for more severe forms of endometriosis. There are few data in the literature about the influence of psychological factors and psychiatric comorbidities on the effectiveness of treatments. It is important to evaluate the presence of previous psychiatric diseases in order to select the most appropriate treatment for the patient. Keywords: endometriosis, pelvic pain, anxiety, depression